A STUDY OF THE PHYTOCHEMICAL CONSTITUENTS IN THE LEAF FRACTIONS OF COMBRETUM MOLLE (R.Br. Ex.G.Don) BY GC- MS ANALYSIS - D. KULAWE; S.P. BAKO; D.N. IORTSUUN; H.I. INABO; J. S. HENA, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
The aqueous, n-butanol and the ethyl-acetate fractions of the leaf of Combretum molle were analyzed for their phytochemical content using Gas chromatography –mass spectrometry (GCMS). Ethanol was used as solvent for extraction, after which differential fractionization was carried out using distilled water, ethyl acetate and n-butanol. Aqueous, ethyl-acetate and nbutanol fractions of the leaf of C. molle were screened for secondary chemicals. GC-MS revealed the presence of 17 compounds in the n-butanol leaf fraction, 15 compounds in the ethyl-acetate leaf fraction and 11 compounds in the aqueous leaf fraction.